STIRRING AND NON-STIRRING METHODS USED TO MAKE SYNTHETIC DOLOMITE-BASED EPSOM SALT - TATANG WAHYUDI; BUDHY AGUNG (Puslitbang tekMIRA, 2006)
The increasing need of magnesium sulfate heptahidrat by various industries and the limited availabil- ity of this material in nature are two reasons to produce MgSO4.7H2O synthetically. Basically, such a material can be produced from dolomite. A laboratory scale of dolomite-based epsomite making which employed two crystallization processes was conducted. Those were stirring and non-stirring methods and the results showed that stirring one yielded 98.2312 to 98.7244 % MgSO4.7H2O salt. The non-stirring method produced salts of 97.5929 – 99.0378%. Yet prior to salt processing, magne- sium sulfate solution was evaporated at 100 – 110°C to get solution densities around 1.35, 1.38 and1.4 g/ml. The bigger the density the bigger the MgO and SO3 contents